1981
DOI: 10.1017/s0021859600035784
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the quantity of formaldehyde applied at ensiling and of urea supplementation at feeding on the utilization of red clover silages by young growing cattle

Abstract: Six silages were prepared from a primary growth of red clover using additives of 2 1 formic acid/t fresh crop together with formaldehyde at 0, 16, 34, 52, 77 or 117 g/kg crude protein (CP) in the crop. These silages were offered to appetite, either alone or with a urea supplement at 19-4 g/kg total dietary dry matter (D.M.), to 60 British Friesian steer calves with an initial mean live weight of 106 kg.Formaldehyde treatment restricted silage fermentation, the effect increasing with level of application. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
3

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
5
10
3
Order By: Relevance
“…Cellulose digestibility was significantly depressed by paraformaldehyde addition in ryegrass, but not in lucerne. The reduction in cellulose digestibility probably arose from a reduced rate of cellulose digestion in the rumen, as reported for formalin-treated silages by Wilkins, Wilson & Cook (1974) and Kaiser (1979). This difference in response between crop species may, as suggested by Kaiser (1979), be due to differences in the composition of the cell-wall constituents between grasses and legumes, resulting in less binding of HCHO with cell-wall constituents in lucerne.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Cellulose digestibility was significantly depressed by paraformaldehyde addition in ryegrass, but not in lucerne. The reduction in cellulose digestibility probably arose from a reduced rate of cellulose digestion in the rumen, as reported for formalin-treated silages by Wilkins, Wilson & Cook (1974) and Kaiser (1979). This difference in response between crop species may, as suggested by Kaiser (1979), be due to differences in the composition of the cell-wall constituents between grasses and legumes, resulting in less binding of HCHO with cell-wall constituents in lucerne.…”
Section: Discussionmentioning
confidence: 70%
“…The failure of paraformaldehyde to increase silage intake was associated with relatively high intakes of the untreated silages, which were reasonably well preserved. The intakes of well fermented silages made from untreated crops, as characterized by a low pH and with <10% of total-N as ammonia, have frequently not been increased when formic acid (Wilkins & McLeod, 1970) or formalin (Wilkins, Wilson & Cook, 1974;Kaiser, 1979) have been employed as additives. Although the untreated lucerne had a pH of 5-0 and acid content of 7% of D.M., ammonia-N content remained relatively low at 12 % of total N.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is supported by the findings of Osbourn et al (1978), that substituting fish meal for urea in a diet of maize silage increased the flow of undegraded dietary protein and total protein into the small intestine of calves; and those of Kaiser et al (1978), that ensiling red clover with a formic-acid/formaldehyde mixture containing 30 to 40 g formaldehyde/kg crude protein increased N retention in calves, relative to the same red clover ensiled with formic acid alone. Amongst the legumesupplemented diets, the highest daily LWG (0-93 kg/head) was sustained by the diet containing red clover silage with formic acid and formaldehyde, on a relatively low intake of DOM but a high food conversion efficiency (FCE).…”
Section: Animal Performance and Feed Conversionmentioning
confidence: 68%
“…However, the solubility of the N in ensiled red clover may be reduced by the addition of formaldehyde during ensiling (Kaiser, England and Gibbs, 1978). Red clover silage conserved with formic acid will usually have a high total N content but this N is highly degradable in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…In the present trial the depression in intake may in part be linked with a depression in digestibility. Lonsdale et al (1977) suggested that the low intake of silage preserved with high levels of formaldehyde could be associated with a lack of rumen-degradable N, although recent evidence from Kaiser (1979) indicates that the effect is complicated by the direct action of formaldehyde on digestion. In the present trial the reduced performance of calves given formaldehydepreserved silage as the sole feed was not present when the silages were supplemented with barley/fish meal but was again apparent when the silages were supplemented with dried grass.…”
Section: Discussionmentioning
confidence: 99%